A CHRISTIAN PLAGUE: HOMOPHOBIA - Motti, Luiz (2007)
Homosexuals are the most hated minority group amongst all the others, and the explanation for the existence of such intolerance is that the love between people of the same sex has secularly been considered a hideous crime, condemned as an abominable sin, hidden through a real conspiracy of silence. This "racism anti-homosexual", scientifically labeled as homophobia, resulted in the internalization and institutionalization of intolerance in a significant part of the heterosexist society, starting with the repression inside the proper family, inside the churches and the academy, inside political parties, including entities working in the defense of human rights and inside the governmental power. The cultural and institutional homophobia also contaminates the proper victims: most gays, lesbians and transgenders live in some kind of identity vacuum and under the perverse effect of alienation, with low self-steem, being incapable of actions in the defense of their own citizenship. One of the priorities to revert this perverse picture is to de-construct the religious taboos that diabolize the love between people of the same sex, stimulating the different churches to promote pastorals that are specifically applied to the sexual minorities, not relinquishing the implementation of governmental affirmative actions aiming at the full citizenship building of the homosexual community.